Modeling Infectious Bursal Disease Virus (IBDV) Antigenic Drift In Vitro - Amin S. Asfor; Vishwanatha R. A. P. Reddy; Salik Nazki; Joanna Urbaniec; Andrew J. Brodrick; Andrew J. Broadbent (Viruses, 2022)
Infectious bursal disease virus (IBDV) vaccines do not induce sterilizing immunity, and vaccinated birds can become infected with field strains. Vaccine-induced immune selection pressure drives the evolution of antigenic drift variants that accumulate amino acid changes in the hypervariable region (HVR) of the VP2 capsid, which may lead to vaccine failures. However, there is a lack of information regarding how quickly mutations arise, and the relative contribution different residues make to immune escape. To model IBDV antigenic drift in vitro, we serially passaged a classical field strain belonging to genogroup A1 (F52/70) ten times, in triplicate, in the immortalized chicken B cell line, DT40, in the presence of sub-neutralizing concentrations of sera from birds inoculated with IBDV vaccine strain 2512, to generate escape mutants. This assay simulated a situation where classical strains may infect birds that have suboptimal vaccine-induced antibody responses. We then sequenced the HVR of the VP2 capsid at passage (P) 5 and 10 and compared the sequences to the parental virus (P0), and to the virus passaged in the presence of negative control chicken serum that lacked IBDV antibodies. Two escape mutants at P10 had the same mutations, D279Y and G281R, and a third had mutations S251I and D279N. Furthermore, at P5, the D279Y mutation was detectable, but the G281R mutation was not, indicating the mutations arose with different kinetics.